Second-order coupled integral boundary value problems at resonance - Du, Yue; Cui, Yujun (Nonlinear Analysis: Modelling and Control, 2026)
This paper investigates the existence of positive solutions for a resonant system of nonlinear differential equations subject to coupled integral boundary conditions involving Riemann–Stieltjes integral. Our analysis is based on Leggett–Williams norm-type theorem for coincidence equations due to O’Regan and Zima. By employing a general abstract framework, we obtain new existence criteria that complement and extend recent results in the literature.
Keywords: positive solution; coupled integral boundary value problem; Riemann–Stieltjes integral; resonance